Single Nucleotide Polymorphisms Associated with Wine Fermentation and Adaptation to Nitrogen Limitation in Wild and Domesticated Yeast Strains - Martinez-Fernandez, C; Villalobos-Cid, M; Kessi-Perez, E (BioMed Central Ltd, 2023)
For more than 20 years, Saccharomyces cerevisiae has served as a model organism for genetic studies and molecular biology, as well as a platform for biotechnology (e.g., wine production). One of the important ecological niches of this yeast that has been extensively studied is wine fermentation, a complex microbiological process in which S. cerevisiae faces various stresses such as limited availability of nitrogen. Nitrogen deficiencies in grape juice impair fermentation rate and yeast biomass production, leading to sluggish or stuck fermentations, resulting in considerable economic losses for the wine industry. In the present work, we took advantage of the “1002 Yeast Genomes Project” population, the most complete catalogue of the genetic variation in the species and a powerful resource for genotype-phenotype correlations, to study the adaptation to nitrogen limitation in wild and domesticated yeast strains in the context of wine fermentation. We found that wild and domesticated yeast strains have different adaptations to nitrogen limitation, corroborating their different evolutionary trajectories. Using a combination of state-of-the-art bioinformatic (GWAS) and molecular biology (CRISPR-Cas9) methodologies, we validated that PNP1, RRT5 and PDR12 are implicated in wine fermentation, where RRT5 and PDR12 are also involved in yeast adaptation to nitrogen limitation. In addition, we validated SNPs in these genes leading to differences in fermentative capacities and adaptation to nitrogen limitation. Altogether, the mapped genetic variants have potential applications for the genetic improvement of industrial yeast strains. © 2023, The Author(s).